UPAYA ASEAN DALAM MENANGGAPI NON-COMMUNICABLE DISEASES (PENYAKIT TIDAK MENULAR) DI INDONESIA PADA TAHUN 2016-2020 - Anisa Meisafiradiani (2021)
This research focuses on one of the health issues problem and international organizations. At this time, health issues became one of an interesting study for international relations major, this happened because a diseases could be a threat to human security. The high number of deaths caused by non-communicable diseases in Southeast Asia and Indonesia has forced ASEAN and Indonesia to make various efforts to prevent and control non-communicable diseases. ASEAN has health cooperation which is listed in the ASCC pillar. After the establishment of the post-2015 health development agenda, ASEAN established a work program which is divided into four Health Clusters. One of the Health Clusters has a focus on non-communicable diseases which later would be implemented into Project Activities as a form of cooperation to response, prevent and overcome non-communicable diseases. As a regional organization, ASEAN has its own role to help its member countries, while the role of ASEAN in responding to the issue of non-communicable diseases in Indonesia by being a arena such as facilitating meetings, instruments (tools), aligning and recommending policies. In this research, the author uses a qualitative method with descriptive case study approach. Data that has been obtained comes from interview and literature study, such as journal, article, book, and internet. The result of this paper sees that with the cooperation of non-communicable diseases, ASEAN indirectly gives an influence or impact for Indonesia in doing a coordinate and cooperation on national level. Keyword: Non-Communicable Diseases, ASEAN, Role of International Organizations, Human Security.